Privacy-preserving keyword search on encrypted database - Fauzan Nadhif Muhammad (Nanyang Technological University, 2020)
Privacy issue is prevalent in web technology specifically in search engine. Data are collected for the purpose of personalized ads and recommendations by search engine providers. Current solutions provide privacy by trust and not by design. One of the solutions to this problem is an encryption scheme called Searchable Symmetric Encryption (SSE). This project aims to implement a working prototype of client-server model of SSE. The prototype was developed as a Web Application written in Java using a code library called Clusion for the implementation of the SSE methods. A typical SDLC process was followed to ensure the quality and correctness of the application. The implementation was divided into 3 parts: the web server, the web client or browser, and the store client. The result showed the possibility of client-server model of SSE system with minimum requirement and dependency in the client. This implies the possibility for large-scale search engine such as Google to take on this kind of approach and provide privacy preserving search service. A space saving method of encryption can be done to optimize the performance of the system in future studies.